Aplicação clínica da ultrassonografia craniana com doppler em crianças prematuras de muito baixo peso - Gabriel, Marta Lúcia (2010)
Transcranial Doppler sonography is the technique more designate to detect intracranial hemorrhage (ICH) and periventricular leukomalacia (PVL) among preterm. This technique evidence the most important cerebral arteries, mainly arteries the circle of Willis, obtaining blood flow arteries resistance index (RI), becoming upset in cranial hemorrhage and hypoxic-ischemic injuries. Objectives: 1. Investigate the clinical application of Doppler sonography in detection of cerebral lesions in very low birth weight neonates. 2. Evaluate the prognosis considering severity and death according to the presence of changes in cerebral arteries detected by Doppler in these neonates. Casuistics and Methods: A total of 50 preterm infants with gestational age varying between 29 and 32 weeks (30.8  1.5 weeks) and birth weigh 550 to 1.500g (1.179  288g) were submitted to four transcranial Doppler sonography during the intervals between 1st to 5th day of life, 10th to 17th, 18th to 30th, and 30th to 44th days of life. The preterm was submitted to the anterior and transtemporal fontanelle technique with asepsis care of equipment and operator. Results: Cerebral lesions in 16 (32%) preterm, 11 (22%) cases of intracranial hemorrhage, 4 (8%) of periventricular leukomalacia, and 1(2%) of cerebral toxoplasmosis were detected. The study with Doppler demonstrated that the value of RI varied according to the time of performing exam. The mean value of RI in the anterior, middle, and posterior cerebral arteries of preterm with intracranial hemorrhage (n = 11) increased of the first to third exam. There was a statistically significant difference among mean values of RI of the anterior and posterior cerebral arteries (p = 0.001 and p = 0.043, respectively) of preterm without cerebral lesions and with ICH only the first exam. Conclusions: The transcranial Doppler sonography in very low birth weigth neonates is useful in detection of cerebral lesions as intracranial hemorrhage, periventricular leukomalacia, and cerebral toxoplasmosis. Changes of RI of the anterior, middle, and posterior cerebral arteries detected by Doppler, although nonpredictor of death, are related with severity of the clinical presentation in these neonates.